MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN SIKAP SOSIAL SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN SAINS TEKNOLOGI DAN MASYARAKAT (STM) POKOK BAHASAN MEMAHAMI UANG DAN PERBANKAN MATA PELAJARAN EKONOMI DI KELAS X SMA NEGERI 1 SALAM BABARIS KABUPATEN TAPIN - Rani Budiarti (JURNAL SOCIUS, 2014)
Critical thinking skills of students are still lack. Students social attitude contain honestly, discipline, responsibility, toleration, mutual cooperation, mannered, and self-confident attitudes on interacting effectively with social and natural surrounding on range interaction and the existence are also still lack.This study used action research method (PTK) through the stages of planning, implementation, observation, and reflection. This research was conducted in two cycles. Cycle I consists of 2 sessions. Cycle II consists of one session. The results showed that the critical thinking skills of students in groups and individually increased in the second cycle compared to pevious cycles. The mean score in the cycle II increased compared with the cycle I of 72 from 62.The classical completeness in cycle II reaches82% of the previous in the cycle I that only 66,17%. While individual mastery learning in the cycle II only reaches75% of the previous which only reached 47%. Overall, the results of the action on the second cycle has increased an average value of7,46% of the cycle I. For the social attitudes of students, an increase in the percentage of both categories in the classical social attitudes become 82% in the cycle II of the previous in the cycle I that only 56%. While individually 61% of students Into the category of social attitudes in both the cycle I and increased in the cycle II to 89.Key Words : Critical Thingking Skills, Social Attitudes, Learning Model Science Technology and Society (STM), Economy